DS8000 copy services - Westphal, Axel (IBM Corporation, International Technical Support Organization, 2017)
Abstract This IBM® Redbooks® publication helps you plan, install, tailor, configure, and manage Copy Services on the IBM DS8000® operating in an IBM z Systems® or Open Systems environment. This book helps you design and implement a new Copy Services installation or migrate from an existing installation. It includes hints and tips to maximize the effectiveness of your installation, and information about tools and products to automate Copy Services functions. It is intended for anyone who needs a detailed and practical understanding of the DS8000 Copy Services.
Number on resource description page: SG24836700. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed June 29, 2017)
Keywords: Storage area networks (Computer networks); Computer network architectures; Information storage and retrieval systems; Information Systems; Réseaux de stockage (Informatique); Réseaux d'ordinateurs; Architectures; Systèmes d'information